AGILE MODEL-BASED SYSTEMS ENGINEERING COOKBOOK - improve system development by applying proven... recipes for effective agile systems engineering. - DOUGLASS, BRUCE (PACKT PUBLISHING LIMITED, 2022)
Get up to date with the latest recipes for applying agile methodologies and techniques in model-based systems engineering (MBSE) and manage the growing complexity of systems in your organization with ease. Purchase of the print or Kindle book includes a free eBook in PDF format. Key Features Use this updated edition to learn how Agile and MBSE work iteratively and overcome system complexity Develop key systems engineering products and achieve enterprise objectives with step-by-step recipes Build efficient system engineering models using tried and trusted best practices Book DescriptionAgile MBSE can help organizations manage change while ensuring system correctness and meeting customers' needs. But deployment challenges have changed since our first edition. The Agile Model-Based Systems Engineering Cookbook's second edition focuses on workflows - or recipes - that will help MBSE practitioners and team leaders address practical situations that are part of deploying MBSE as part of an agile development process across the enterprise. In this 2nd edition, the Cameo MagicDraw Systems Modeler tool - the most popular tool for MBSE - is used in examples (models are downloadable by readers). Written by a world-renowned expert in MBSE, this book will take you through systems engineering workflows in the Cameo Systems Modeler SysML modeling tool and show you how they can be used with an agile and model-based approach. You'll start with the key concepts of agile methods for systems engineering. Next, each recipe will take you through initiating a project, outlining stakeholder needs, defining and analyzing system requirements, specifying system architecture, performing model-based engineering trade studies, all the way to handling systems specifications off to downstream engineering. By the end of this MBSE book, you'll learn how to implement systems engineering workflows and create systems engineering models. What you will learn Learn how to apply modelling to create and manage important engineering data Apply agile methods to develop systems engineering specifications Communicate decisions with downstream subsystem implementation teams Coordinate with engineers from other disciplines Apply MBSE practices to problems within simple systems or large systems Ensure accurate systems models via tests, simulation, and verification Who this book is for If you are a systems engineer who wants to pursue model-based systems engineering in an agile setting, this book will show you how you can do that without breaking a sweat. Fundamental knowledge of SysML is necessary; the book will teach you the rest.